Lupus Low Disease Activity State Associated with Lower Fatigue : Preeliminary Study - Ryan Ardian Saputro; Santi Andayani; Stefanie Yuliana Usman; Laniyati Hamijoyo (Indonesian Rheumatology Association, 2019)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease with heterogeneous clinical manifestations including fatigue. Previous studies aimed at proving the relationship between fatigue and SLE disease activity showed conflicting results. In 2015, Asia Pacific Lupus Collaboration (APLC) developed low disease activity criteria, named Lupus Low Disease Activity State (LLDAS). Patients who spend more time in LLDAS have significantly lower morbidity. This study aimed to evaluate the association between disease activity based on LLDAS and fatigue. Methods: This is a analytical cross-sectional study. Subjects were SLE patients at rheumatology clinic in Dr. Hasan Sadikin Hospital, Bandung during June-January 2018. Subjects were evaluated based on LLDAS criteria and divided into 2 groups: LLDAS and non-LLDAS. Fatigue status of the subjects was assessed with Fatigue Severity Scale (FSS). Results: A hundred and thirty-three subjects were included in this study, divided into 63 subjects in LLDAS group and 60 subjects in non-LLDAS group. Nineteen subjects (30.2%) in LLDAS group had fatigue and 39 subjects (65%) in non-LLDAS had fatigue. There was a significant association between LLDAS and fatigue (p< 0.001). Nonetheless, fatigue level in LLDAS group was still high since disease activity was not the only factor related to fatigue. Fatigue may be a distinct clinical manifestation of neuropsychiatric lupus and may be independent of lupus disease activity Conclusions: There was a significant association between LLDAS and fatigue showed by lower fatigue level was found in the LLDAS group than in the non-LLDAS group. Keywords: Systemic lupus erythematosus, disease activity, Lupus Low Disease Activity State, fatigue